Economic Development: Development Theories and Their Implementation in Indonesia - Sifah Faoziah; Indri Nailatul Ma'rifah; Hudallah Hudallah (Lentera Demokrasi: Jurnal Ilmu Sosial, Politik, Hukum, Ekonomi dan Pemerintahan, 2025)
Economic development is a nation’s effort to improve the welfare of its people by increasing income levels, expanding equal opportunities, and transforming the economic structure. For Indonesia, economic development is of great importance because it can help reduce poverty, create employment opportunities, and enhance the nation’s competitiveness at the international level. However, economic development is not solely about increasing economic growth figures. In reality, challenges remain in the form of regional disparities, social inequality, and difficulties in maintaining environmental sustainability. Several studies also indicate that economic growth in Indonesia has not been evenly distributed across regions, and that inclusive and environmentally sustainable growth still requires significant improvement. Therefore, it is essential to study theories of economic development and examine their application in the Indonesian context so that the development process can become more equitable, inclusive, and sustainable.